Community displacement: an injustice resulting from urban regeneration initiatives in the Johannesburg CBD - Neluheni, Mudzunga Gina (My University, 2019)
In South Africa, regeneration is a key instrument towards achieving spatial efficiency and inclusion in metropolitan cities. Nonetheless, it often results in the process of gentrification associated with displacement. Many studies have overlooked the qualitative nature of displacement, especially when induced by development activities. Therefore, negating the consequential experiences of people in a moment of gentrification. This study seeks to demonstrate how gentrification-related displacement affects the wellbeing of the working class, by considering and analyzing their lived experiences. Therefore, steering attention to a critical displacement discourse. The case study is Maboneng Precinct, a neighbourhood created through the regeneration of a section of old Jeppestown. The method used is qualitative with a phenomenological narrative of experiences. An analysis of the findings from the interviews with displaced and remaining working-class residents in Maboneng indicate the capacity of the participants to persist through the pressures of gentrification-related displacement. All in effort to maintain their social and economic well-being in a changing environment. Subsequently, I led a desktop review of the South African Integrated Development Framework (IUDF) to demonstrate the extent to which it addresses the issue of gentrification-related displacement. The framework indicates displacement as a reality in South African urban settings, prompted by spatial transformative strategies. Thus, IUDF flags conditions that need fixing to avoid further displacement of the urban working-class from neighbourhoods undergoing regeneration. Therefore, asserting the government’s responsibility to budget appropriately for resources to be available to follow through with urban development that is efficient and inclusive
University of Witwatersrand School of Architecture and Planning Masters in Development Planning May 2019